1967
DOI: 10.1177/001872086700900610
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Values of Energy Expenditure Rate from Observed Values of Heart Rate

Abstract: Different bases upon which linear regression equations can be constructed for estimating values of energy expenditure rate from observed values of heart rate are examined. Approximately 100 different regression equations corresponding to different bases were developed from 510 observations made of 11 different tasks. The regression equations constructed on the various bases are compared with one another and with respiratory calorimetry in terms of the experimental error which each introduces into the estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Since oxygen demand is difficult to measure directly during competitive dance performance, this study relies on the relationship which has previously been established between heart rate (HR) and oxygen consumption (M°2 during submaximal exercise (Wyndham et al, 1959;Astrand and Saltin, 1961;Molhotra et al, 1963;Andrews, 1967;Datta and Ramanathan, 1969). During low-intensity work a linear function fits both oxygen uptake and HR plots against workload, but at high workloads the curve has been described as an exponential function.…”
Section: Introductionmentioning
confidence: 99%
“…Since oxygen demand is difficult to measure directly during competitive dance performance, this study relies on the relationship which has previously been established between heart rate (HR) and oxygen consumption (M°2 during submaximal exercise (Wyndham et al, 1959;Astrand and Saltin, 1961;Molhotra et al, 1963;Andrews, 1967;Datta and Ramanathan, 1969). During low-intensity work a linear function fits both oxygen uptake and HR plots against workload, but at high workloads the curve has been described as an exponential function.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between HR and VO 2 has become widely used in the evaluation of work when it is difficult or impractical to measure oxygen uptake directly (Andrews, 1967;Blanksby and Reidy, 1988;Fitchett, 1985;Karvonen et al, 1957). This relationship is also commonly used to predict VO 2max from the extrapolation of HR recorded at low-intensity Running Speed (mph) FIGURE 1 Heart rate and oxygen consumption (VO 2 ) pre-and postintense exercise at four steady-state running speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Such evaluation relies on numerous investigations that have previously identified a linear relationship between HR and VO 2 during submaximal exercise (Andrews, 1967;Astrand and Saltin, 1961;Bunc etal., 1988;Collins etal., 1991;Datta and Ramanathan, 1969;Kline et al, 1987;Legge and Banister, 1986;Molhotra et al, 1963;Wyndham et al, 1959). It is accepted that long-term training can change the HR and VO 2 relationship through an increase in stroke volume, total hemoglobin, or an increased tissue oxygen utilization (Astrand and Rodahl, 1977 Recent research has suggested that the accepted V0 2 to HR linear relationship is not as stable as originally suggested.…”
Section: Discussionmentioning
confidence: 99%